Biochemical and structural characterization of hepatitis A virus 2C reveals an unusual ribonuclease activity on single-stranded RNA. Issue 16 (10th August 2022) - Chen, Pu; Wojdyla, Justyna Aleksandra; Colasanti, Ombretta; Li, Zhijian; Qin, Bo; Wang, Meitian; Lohmann, Volker; Cui, Sheng
Abstract: The HAV nonstructural protein 2C is essential for virus replication; however, its precise function remains elusive. Although HAV 2C shares 24–27% sequence identity with other 2Cs, key motifs are conserved. Here, we demonstrate that HAV 2C is an ATPase but lacking helicase activity. We identified an ATPase-independent nuclease activity of HAV 2C with a preference for polyuridylic single-stranded RNAs. We determined the crystal structure of an HAV 2C fragment to 2.2 Å resolution, containing an ATPase domain, a region equivalent to enterovirus 2C zinc-finger (ZFER) and a C-terminal amphipathic helix (PBD). The PBD of HAV 2C occupies a hydrophobic pocket (Pocket) in the adjacent 2C, and we show the PBD–Pocket interaction is vital for 2C functions. We identified acidic residues that are essential for the ribonuclease activity and demonstrated mutations at these sites abrogate virus replication. We built a hexameric-ring model of HAV 2C, revealing the ribonuclease-essential residues clustering around the central pore of the ring, whereas the ATPase active sites line up at the gaps between adjacent 2Cs. Finally, we show the ribonuclease activity is shared by other picornavirus 2Cs. Our findings identified a previously unfound activity of picornavirus 2C, providing novel insights into the mechanisms of virus replication.